Unlocking Career Bliss How Communication Skills And Adaptability Fuel Satisfaction In Turbulent Job Markets - Robiansyah; Aini, Rohana Nur; Erwin Setiawan (Jurnal Ragam Pengabdian, 2026)
This study analyzes the relationship between career satisfaction, communication skills, and career adaptability. The dynamic global environment requires the workforce to have an adaptive attitude to meet the demands of change. Career patterns have become increasingly diverse, and successful career development largely depends on individual initiative, soft skills, and the ability to adapt in the world of work. This study analyzes the direct and indirect effects on career satisfaction among graduates of the Faculty of Economics and Business, Mulawarman University, using purposive sampling with 272 respondents. The results indicate that communication skills have a positive and significant effect on career adaptability and career satisfaction. Furthermore, career adaptability positively and significantly affects career satisfaction and mediates the relationship between communication skills and career satisfaction. These findings highlight the importance of communication skills comprising English proficiency, interpersonal/oral skills, and writing abilities and career adaptability as predictors of career satisfaction.